MuSK EAMG: Immunological Characterization and Suppression by Induction of Oral Tolerance - Reuveni, Debby; Aricha, Revital; Souroujon, Miriam C.; Fuchs, Sara (Frontiers in Immunology, 2020)
Myasthenia gravis (MG) with antibodies to the muscle-specific receptor tyrosine kinase (MuSK) is a distinct sub-group of MG, affecting 5–8% of all MG patients. MuSK, a receptor tyrosine kinase, is expressed at the neuromuscular junctions (NMJs) from the earliest stages of synaptogenesis and plays a crucial role in the development and maintenance of the NMJ. MuSK-MG patients are more severely affected and more refractory to treatments currently used for MG. Most patients require long-term immunosuppression, stressing the need for improved treatments. Ideally, preferred treatments should specifically delete the antigen-specific autoimmune response, without affecting the entire immune system. Mucosal tolerance, induced by oral or nasal administration of an auto-antigen through the mucosal system, resulting in an antigen-specific immunological systemic hyporesponsiveness, might be considered as a treatment of choice for MuSK-MG. In the present study we have characterized several immunological parameters of murine MuSK-EAMG and have employed induction of oral tolerance in mouse MuSK-EAMG, by feeding with a recombinant MuSK protein one week before disease induction. Such a treatment has been shown to attenuate MuSK-EAMG. Both induction and progression of disease were ameliorated following oral treatment with the recombinant MuSK fragment, as indicated by lower clinical scores and lower anti-MuSK antibody titers.